Premixed hydrogen combustion: kinetic predictions of flame behaviour - Gonçalves, Ailton Donadony Fernandes (2022)
In this final master's work, it was intended to analyze the involvement of hydrogen as an energy carrier and fuel, with emphasis on its combustion properties, analysis to radicals and chemical species, in mixtures with other species, namely methane (CH4 ), carbon dioxide (CO2) and natural gas (NG). The studies were carried out through numerical simulations, with the kinetic mechanisms GRI-MECH 3.0, San Diego Mech, Qin Mech, AramcoMech_1.3 and Boivin Mech, performed in the programming environment Python, using the library Cantera. Studies were performed on the adiabatic flame temperature (Tb), the laminar flame speed (SL) and the flame stability and operating limits. The influence of 4 parameters, fuel composition, equivalence ratio (ϕ), premix temperature with air (Tu) and the system pressure (P) were studied. Similar behaviour was observed between adiabatic flame temperature and flame speed with respect to the equivalence ratio, where the maximum value is reached in the rich mixing zone. For the influence of the premix temperature, it was observed that its increase generates an increase in Tb and SL, while the increase in pressure generates an increase in adiabatic temperature and a decrease in flame speed. When using mixtures of H2 with CH4 and CH4/CO2 , it is observed that both adiabatic temperature and flame speed show decreases, and their maximum values approach the stoichiometry. Empirical equations have been proposed to describe the adiabatic temperature of pure hydrogen flames as a function of equivalence ratio, premix temperature and pressure. Regarding flame stability and operating limits, the influence of H2 content in a hydrogen-enriched natural gas (HENG) blend was evaluated. Results show an increase in flame stability by the addition of H2 .